2023
DOI: 10.1021/acs.molpharmaceut.2c00824
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of Photodynamic Therapy/Sonodynamic Therapy/Sono-Photodynamic Therapy of Chlorin e6 and Other Applications

Abstract: Chlorin e6 (Ce6) has been extensively researched and developed as an antitumor therapy. Ce6 is a highly effective photosensitizer and sonosensitizer with promising future applications in photodynamic therapy, dynamic acoustic therapy, and combined acoustic and light therapy for tumors. Ce6 is also being studied for other applications in fluorescence navigation, antibacterials, and plant growth regulation. Here we review the role and research status of Ce6 in tumor therapy and the problems and challenges of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 74 publications
0
27
0
Order By: Relevance
“…Chemical structures and optical properties of molecular sonosensitizers that are used in this study are shown in Figure . They are selected based on the existing literature including the most commonly studied one to the least studied one. They include chlorine e6, protoporphyrin IX, rose bengal, curcumin, IR780 iodide, emodin, doxorubicin, levofloxacin, tannic acid, epigallocatechin gallate (EGCG), and catechin. We have selected tannic acid, EGCG, and catechin due to their well-known therapeutic applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical structures and optical properties of molecular sonosensitizers that are used in this study are shown in Figure . They are selected based on the existing literature including the most commonly studied one to the least studied one. They include chlorine e6, protoporphyrin IX, rose bengal, curcumin, IR780 iodide, emodin, doxorubicin, levofloxacin, tannic acid, epigallocatechin gallate (EGCG), and catechin. We have selected tannic acid, EGCG, and catechin due to their well-known therapeutic applications.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound has a great potential for sonodynamic therapy with the wireless treatment option in a range of human diseases. This therapeutic approach requires sound-responsive materials, commonly known as sonosensitizers. Well-known sonosensitizers include microbubbles, piezoelectric nanoparticles, and some selected organic small molecules. Among them, microbubbles are the most popular due to their high sound-responsive property, although their large size restricts the in vitro / in vivo targeting options. Similarly, piezoelectric nanoparticles are promising, although their design with high sound-responsive performance is challenging. In contrast, organic small molecule-based sonosensitizers are attractive due to their clear chemical structure and smaller size. However, they must have specific functional groups to offer the sonodynamic activity, and a clear understanding of the origin of such activity is yet to be established . Moreover, small molecule sonosensitizers are hydrophobic/organic in nature with low water solubility and low cell/tumor specificity and have a short circulation time in physiological conditions …”
Section: Introductionmentioning
confidence: 99%
“…At present, a lot of PDT drugs or PDT drug-loaded nanoparticles like porphyrin analogues, heptamethine cyanine dye, and phenothiazine derivatives were discovered to solve the internal defects of traditional PDT drugs like excessive blood metabolism, low ROS yield ratio, and no tumor-targeting capacity. Among these superior PDT drugs, heptamethine cyanine dye analogues like IR-780 and MHI-148 derived from clinically approved diagnostic medicine indocyanine green was the most potent, since these molecules selectively accumulate at the tumors and can be excited by near-infrared laser with 8 mm–1 cm depth of tissue penetration. , However, the efficacy of these heptamethine cyanine dyes or these drug-loaded nanoparticles is still seriously restricted due to their disability to regulate the exogenous hypoxia and high PD-L1 and TGF-β expression immune-suppression tumor microenvironment (TME), which then leads to limited ROS generation and possibly further augmented PD-L1 expression mediated by PDT-induced higher IFN-γ expression in vivo . , Currently, to our best knowledge, few PDT drugs except Verteporfin and SORgenTAM are proven to possess the ability to decrease PD-L1 expression or reverse the tumor hypoxia microenvironment. However, these PDT drugs or nanoparticles still could not solve masses of problems faced by PDT simultaneously. , Therefore, further embellishment of heptamethine cyanine dye to construct a better PDT drug or nanoparticle with self-regulated oxygen, PD-L1, and TGF-β capacity is still urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Functional metal-organic skeleton MIL-101-NH2-AL@Ori@Ce6 construction and treatment of tumors is shown in Figure 1. [53][54][55] 2 | EXPERIMENTAL…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our newly designed nano‐drug delivery system may be a promising tumor nano‐drug platform for photochemotherapy combined with chemotherapy. Functional metal–organic skeleton MIL‐101‐NH2‐AL@Ori@Ce6 construction and treatment of tumors is shown in Figure 1 53–55 …”
Section: Introductionmentioning
confidence: 99%